Utilization of Digital Technology by Political Volunteers in the 2024 Presidential Election to Enhance Electability Under the Open Proportional Electoral System - Lestiyani, Tri Endah Karya; Syauket, Amalia (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
Open elections, which allow voters to directly choose presidential candidates, have become increasingly effective with the presence of political volunteers who utilize social media and online platforms to facilitate interaction between the presidential candidates and voters. This study aims to analyze how digital technology can serve as a powerful tool for political volunteers to enhance electability in open elections. The object of this research is the 2024 presidential contest, using secondary data sources from various relevant references. This study employs a qualitative descriptive approach, emphasizing the collection and analysis of secondary data obtained from academic literature, government reports, credible news outlets, and official websites related to the 2024 presidential election. The method focuses on interpreting patterns, narratives, and digital strategies used by political volunteers to improve candidate visibility and voter engagement. Content analysis was also used to examine how digital platforms were utilized as campaign tools during the electoral process. Academic findings indicate that during the 2024 presidential election, digital technology used by political volunteers significantly strengthened the relationship between candidates and voters through online campaigns. The presence of digital technology facilitated various aspects of open elections, such as improving communication during campaigns and increasing public participation—all aimed at boosting electability. Electability has become a crucial requirement for candidacy and eventual victory.